2023
DOI: 10.1002/dta.3538
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profile, phase I metabolism, and excretion time profile of the new synthetic cathinone 3,4‐Pr‐PipVP

Abstract: Abstract1‐(2,3‐Dihydro‐1H‐inden‐5‐yl)‐2‐(piperidin‐1‐yl)pentan‐1‐one (3,4‐Pr‐PipVP), a novel synthetic cathinone (SCat), was first identified in 2022 in Germany. The product was marketed as 1‐(bicyclo[4.2.0]octa‐1,3,5‐trien‐3‐yl)‐2‐(pyrrolidin‐1‐yl)pentan‐1‐one (3,4‐EtPV), a substance not covered by the German New Psychoactive Substances Act (NpSG). Although originally intended to be an exploratory new synthetic cathinone containing the novel bicyclo[4.2.0]octatrienyl function, the compound was subsequently co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…150 Furthermore, and in contrast to its nonsubstituted analogue α-piperidinevalerophenone (α-PpVp), 3,4-propylene-2-(1-piperidinyl)valerophenone (3,4-Pr-PipVP) which contains a propylene bridge, results in equal potency at inhibiting DAT vs SERT. 151 The introduction of bulkier substituents in different positions of the aromatic ring also plays a role in the releasing properties of synthetic cathinones. Walther and colleagues demonstrated that bulkier substituent at the metaor para-position of MCAT results in decreased DAT release potency.…”
Section: ■ Structure−activity Relationship Of Synthetic Cathinonesmentioning
confidence: 99%
“…150 Furthermore, and in contrast to its nonsubstituted analogue α-piperidinevalerophenone (α-PpVp), 3,4-propylene-2-(1-piperidinyl)valerophenone (3,4-Pr-PipVP) which contains a propylene bridge, results in equal potency at inhibiting DAT vs SERT. 151 The introduction of bulkier substituents in different positions of the aromatic ring also plays a role in the releasing properties of synthetic cathinones. Walther and colleagues demonstrated that bulkier substituent at the metaor para-position of MCAT results in decreased DAT release potency.…”
Section: ■ Structure−activity Relationship Of Synthetic Cathinonesmentioning
confidence: 99%